SF3B1K700E mutation in human embryonic stem cells causes aberrant expression of immune-related genes - Mahtab Dastpak; Claudia A. Mimoso; Moein Farshchian; Christina L. Paraggio; Claudia E. Leonard; Shanye Yin; Binkai Chi; Kelsey W. Nassar; R. Grant Rowe; Jiuchun Zhang; Zhonggang Hou; George Q. Daley; et al. (PLoS ONE, 2025)
SF3B1, a component of the U2 snRNP pre-mRNA splicing factor, plays a critical role in splicing and is frequently mutated in cancer, particularly hematologic malignancies. We investigated the effects of the most common SF3B1 mutation, heterozygous substitution of Lysine 700 to Glutamate (K700E), in human embryonic stem cells (hESC), using CRISPR-Cas9 to generate heterozygous SF3B1 K700E clones. Interestingly, we observed the upregulation of several key transcription regulators associated with hematopoiesis and a broad range of immune genes in SF3B1 K700E hESCs. Despite differences in the transcriptional and splicing profiles between hESC and myelodysplastic syndrome (MDS) cells harboring the SF3B1 K700E mutation, several common immune gene programs were identified in both cell types. To elucidate the molecular mechanisms underlying dysregulated gene expression in SF3B1 K700E hESCs, we mapped actively engaged RNA polymerase II (RNA Pol II) using Precision Run-On sequencing (PRO-seq). These analyses revealed that the SF3B1 K700E mutation alters RNA Pol II elongation properties. Specifically, we observed a general increase in pause release in SF3B1 K700E hESCs, consistent with recent work in leukemia cells suggesting that the SF3B1 K700E mutation affects early transcription elongation. Taken together, our study identifies several candidate genes that could contribute to the SF3B1 mutated phenotype and clarifies the role for the U2 snRNP and pre-spliceosome assembly on transcription by RNA Pol II. Further, our data suggest that mutations of SF3B1 impact immune gene expression independent of cell type, providing new insights into the role of SF3B1 K700E in hematologic malignancies.